Not as Stable as We Think: A Descriptive Study of 12 Monthly Assessments of Fear of Cancer Recurrence Among Curatively-Treated Breast Cancer Survivors 0–5 Years After Surgery - Custers, José AE; Kwakkenbos, Linda; van der Graaf, Winette TA; Prins, Judith B; Gielissen, Marieke FM; Thewes, Belinda (Frontiers in Psychology, 2020)
Purpose: Previous studies suggest one-third of breast cancer survivors (BCS) experience elevated fear of cancer recurrence (FCR) and that it remains stable. Most studies include long assessment intervals and aggregated group data. This study aimed to describe the individual trajectories of FCR when assessed monthly using both a statistical and descriptive approach. Methods: Participants were curatively-treated BCS 0–5 years post-surgery. Questionnaire data were collected monthly for 12 months. Primary outcome was FCR (Cancer Worry Scale (CWS)). For the descriptive approach, 218 participants were classified as low (CWS ≤13 at each assessment) high (CWS ≥14 at each assessment) or fluctuating FCR (CWS scores above and below cut-off). Latent class growth analysis (LCGA) (n=377) was conducted to identify trajectories over time. Results: 58% of the women reported fluctuating CWS scores, 22% reported a consistently high and 21% consistently low course. Results of the LCGA confirmed the 3 class approach including a stable high FCR group (13%), a low FCR group (40%), and a moderate FCR group (47%). Both the moderate and low scoring groups reported declining scores over time. Younger patients, higher educated patients and those less satisfied with the medical treatment were more likely to belong to the moderate or high trajectory. Conclusions: Assessed monthly, the majority of BCS report fluctuating levels of FCR. Stepped-care models should assess FCR on multiple occasions before offering tailored interventions.